Combining ability for resistance to fall armyworm, Spodoptera frugiperda in tropical maize inbred lines - Nuambote-Yobila, Ovide; Bruce, Anani Y.; Makumbi, Dan; Ogola, Gerphas; Marangu, Charles; Beyene, Yoseph; Mahungu, Nzola-Meso; Boddupalli, Prasanna; Marion-Poll, Frédéric; Calatayud, Paul-André (Springer Nature, 2025)
The fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith), poses a significant threat to food security in sub-Saharan Africa. Identification of resistance in tropical maize germplasm is critical for development of FAW-resistant hybrids, which can be a component of Integrated Pest Management (IPM) strategies. This study assessed the general (GCA) and specific (SCA) combining ability, and reciprocal effects for FAW resistance parameters. Seven inbred lines were evaluated for their per se performance, and four lines were selected and crossed in a full diallel to generate 12 hybrids. Both inbred lines and hybrids were tested under artificial FAW infestation under net house conditions. Five FAW neonates were placed in each plant at the V5 growth stage. Leaf feeding damage and larval survival were assessed 14 days after infestation. Significant differences for leaf feeding damage and larval survival were detected among the lines and hybrids. Inbred lines Mp716, CML125, CML71, and CKSBL10008 showed partial resistance to FAW in terms of leaf feeding damage. Significant GCA, SCA, and reciprocal effects for both traits were detected. Additive genetic effects were more important for leaf feeding damage, while both additive and nonadditive genetic effects were more important than reciprocal effects for larval survival. Heterosis associated with increased resistance, ranged from -0.7% to -38.4% for leaf feeding damage and from -3.6% to -54.4% for larval survival. Inbred lines CML71 and CKSBL10008 were identified as promising parents for biparental populations in maize breeding programs targeting resistance to FAW. Selection methods that improve GCA are important for improvement of resistance to FAW in tropical maize germplasm.